Influencing Factors of Children's Spatial Orientation Competence with the Help of a City Map within a Real Area - Hemmer, Ingrid; Hemmer, Michael; Kruschel, Katja; Neidhardt, Eva; Obermaier, Gabi; Uphues, Rainer (Journal of Geography Education, 2010)
Within this article a research project on influencing factors of children's spatial orientation competence is presented. Partially, the main focus is put on the concept of representation as a theoretical foundation. The research design (preliminary and main investigation) for collecting data of independent variables (e.g. previous knowledge, self-image, spatial intelligence) and dependent variables (orientation competence) as well as the self-developed measuring instrument are explained. Concluding, the study is outlined. Altogether 328 pupils of the 3rd, 4th and 5th grade from all kinds of North Rhine-Westphalian schools have been tested.